Evaluación de la contaminación sonora generada por el tránsito vehicular mediante la elaboración de mapas acústicos en el centro histórico de Arequipa - Alarcon Quispe, Barbara Atenas (2020)
interval, P17Med4 is lower than the ECA in 1.1.dB, the remaining points exceed the ECA with an average of 3.6dB, in the B interval four points are lower than the ECA, and the remaining points exceed the ECA with 4.2dB on average, for the Special Zone in both intervals they exceed the ECA with an average greater than 24dB. The results according to visit; for Residential Zone, interval A exceeds the ECA with an average of 15.9dB, in interval B exceeds the ECA with an average of 17.2dB; for the Commercial Zone, in the interval A the P17Med4 is less than the ECA by 0.1dB, the remaining points exceed the ECA with 3.9dB on average, in the interval B, four points are less than the ECA, the rest of the points are higher than RCT with an average of 4dB. These data show high noise pollution in the study area. Two types of heavy vehicles (van, minivan, bus / combi and truck) and light vehicles (motorcycle, car) were considered, these were counted during the monitoring time at each point; being the vehicle type car that had greater circulation during this time.